2020
DOI: 10.1093/scan/nsaa153
|View full text |Cite
|
Sign up to set email alerts
|

Posterior medial frontal cortex and threat-enhanced religious belief: a replication and extension

Abstract: Research indicates that the posterior medial frontal cortex (pMFC) functions as a ‘neural alarm’ complex broadly involved in registering threats and helping to muster relevant responses. Holbrook and colleagues (2016) investigated whether pMFC similarly mediates ideological threat-responses, finding that down-regulating pMFC via transcranial magnetic stimulation (TMS) caused i) less avowed religious belief despite being reminded of death, and ii) less group bias despite encountering a sharp critique of the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the study reported that these beliefs are vulnerable to targeted neuromodulation through transcranial magnetic stimulation. Holbrook et al (2020) further reported reduced religious belief among participants with a downregulated pMFC when reminded of a relevant threat (such as death), but not under threat-neutral conditions. Therefore, the pMFC may mediate a threat-response to conflict stimuli, and empirical research examining the issue may be supported by evolutionary perspectives (such as reciprocal altruism and group cooperation).…”
Section: Physiological Measurements Of (Financial) Risk-taking and Re...mentioning
confidence: 87%
“…Additionally, the study reported that these beliefs are vulnerable to targeted neuromodulation through transcranial magnetic stimulation. Holbrook et al (2020) further reported reduced religious belief among participants with a downregulated pMFC when reminded of a relevant threat (such as death), but not under threat-neutral conditions. Therefore, the pMFC may mediate a threat-response to conflict stimuli, and empirical research examining the issue may be supported by evolutionary perspectives (such as reciprocal altruism and group cooperation).…”
Section: Physiological Measurements Of (Financial) Risk-taking and Re...mentioning
confidence: 87%